Vocational Education and Training in Europe : Denmark - Andersen, Ole Dibbern [Verfasser]; Kruse, Katrine [Verfasser] (My University, 2016)
This VET in Europe report provides readers with a concise, basic insight into the state of the vocational education and training system of Denmark. It situates the education and training system in Denmark within a broad political, social, economic, and labour market framework. CHAPTER 1. External factors influencing VET; CHAPTER 2. Providing VET in a lifelong learning perspective; CHAPTER 3. Shaping VET qualifications; CHAPTER 4. Promoting participation in VET. (CEDEFOP; BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; I 2.2.1 Westeuropa; Berufsbildung; Berufsbildungssystem; Lebenslanges Lernen; Qualifikationsentwicklung; Ausbildungsbeteiligung; Bildungsfinanzierung; Dänemark